MAJAS DALAM KUMPULAN CERPEN HIMNE BUNGA-BUNGA DI LADANG KARYA CLARA NG - Rahayu, Yayuk Dwi; Sulistyowati, Endang Dwi; Hanum, Irma Surayya (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The study discusses the type of figure of speech and the function of figure of speech in collections of peerlike hymn hymns on Clara ng's field. As for the purpose of this study, to describe the type of majas and the function of figure of speech in clusters of flower hymns in Clara ng's field. The study is a kind of literature type, using a descriptive qualitative approach. The data in this study consists of words and sentences found in packets of flower hymns in Clara ng's field of short stories The flower hymns in the fields, happy birthday, a cidade maravilhosa, monsoon, beautiful eyes, the nostra senhora del rosario. The data-collection techniques in this study use both the punctuation and the logging techniques. The techniques of the data analysis used in this study use stilistica theory through data reduction, data presentation and drawing conclusions. This research produces several conclusions as follows: first there are various types of figure of speech; contention conflict, comparison force, affirmation cooperation, allusion management. The use of the most dominant figure of speech is the hyperbole type comparison and the repetition type confirmation affirmation. Second, the majas function used in the collection of short stories Bunga-Bunga Hymns in Clara Ng's Field; 1) concretizing or clarifying statements, 2) comparing things differently, 3) affirming or reinforcing statements, 4) refining expressions, 5) beautifying statements, 6) insinuating or criticizing a situation.